Release of epigenetic gene silencing by trans-acting mutations in Arabidopsis - Scheid, Ortrun Mittelsten (The National Academy of Sciences, 1998)
Gene silencing in plants inactivates transgenes introduced into plants and/or endogenous homologous genes. This stable but potentially reversible loss of gene activity resembles epigenetic changes that occur in normal development. The stability of silencing implies the involvement of trans-acting components, although none of them have been identified so far. Here we report the finding of second-site mutations interfering with maintenance of the silent state. We mutagenized Arabidopsis thaliana plants carrying a silent transgene encoding hygromycin phosphotransferase (hpt) and therefore show a heritable hygromycin-sensitive phenotype. The M2 generation was screened for hygromycin resistance. Eight putative mutants (som1 to 8) were found that expressed the transgene and transmitted the expressed state to their progeny. All mutations were shown to reactivate a silent transgenic test locus in trans. The level of DNA methylation at the hpt locus and at centromeric repeats was found to be reduced in the som mutants. Complementation crosses indicated complex epigenetic interactions among the som mutant alleles and with the previously described ddm1 allele, which elicits DNA hypomethylation [Vongs, A., Kakutani, T., Martienssen, R. A. & Richards, E. J. (1993) Science 260, 1926–1928]. Som mutants can be classified into three groups: (i) allelic or interacting with ddm1 and with each other (som 1, 4, and 5), (ii) nonallelic with ddm1 and som mutants of group A (som2), and (iii) mutants with slow resilencing after outcrosses, which hinders their classification (som 3, 6, 7, and 8).